Sleep Disturbances in MCI and AD: Neuroinflammation as a Possible Mediating Pathway - Pak, Victoria M.; Onen, S.-Hakki; Bliwise, Donald L.; Kutner, Nancy G.; Russell, Katherine L.; Onen, Fannie (Frontiers in Aging Neuroscience, 2020)
Mild cognitive impairment (MCI) and Alzheimer’s disease (AD) affect a high proportion of the elderly population with increasing prevalence. Sleep disturbances are frequent in those with MCI and AD. This review summarizes existing research on sleep disturbances and neuroinflammation in MCI and AD. Although strong evidence supports various pathways linking sleep and AD pathology, the temporal direction of this central relationship is not yet known. Improved understanding of sleep disturbance and neuroinflammation in MCI and AD may aid in the identification of targets for prevention.